A Critical Review on the Book Child’s Literature in Iran: The University Textbook - Amir Hossein Zanjanbar; Ayoob Moradi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Children’s Literature in Iran is a university textbook that covers most of the topics of the Ministry of Science, for two units of “Children’s Literature” course at the undergraduate level. The author of the book is Mohammad Dehrizi, one of the authors of “Writing” book in high school, a graduate of literature and one of the poets and writers of children and adolescents, who has won several national awards. The book was first published in 2009 under the title Iranian Children and Adolescent Literature, and its new edition was published in 2020. The book has many positive aspects, but due to common methodological weaknesses between this book and many books which are written in the realm of children's literature, the present study prefers to critique this book from an approbation point of view, rather than a critical one. A book has a scientific function to the extent that it can present the paradigms of a theory to the reader in a systematic hierarchy. Therefore, the main purpose of this article is to examine the method of systematizing the paradigms introduced in the book. In this regard, the book is reviewed in six areas: education, methodology, content, editing, chaptering, and aesthetics. This research, for the first time in Iran, reviews a book in the field of theoretical literature for children and adolescents.